Memory Functions of Death Portraits in Miniature Painting and Early Photography (KULT_online, 2020)
In her art historical dissertation Patrizia Munforte sets out the impact of miniature painting on early photography and their significance as media of remembrance in North America after 1839. The main research subject is the death portrait – painted and photographed – and its different forms of presentation. Munforte analyzes the unique process, the materiality, and the principle of likeness as important characteristics for the image and its memory function in the context of cultural and social change.